Ciprofloxacin enhances the biofilm formation of Staphylococcus aureus via an agrC-dependent mechanism - Luo, Zhao-xia; Li, Yuting; Liu, Mei-fang; Zhao, Rui (Frontiers in Microbiology, 2023)
Staphylococcus aureus readily forms biofilms on host tissues and medical devices, enabling its persistence in chronic infections and resistance to antibiotic therapy. The accessory gene regulator (Agr) quorum sensing system plays a key role in regulating S. aureus biofilm formation. This study reveals the widely used fluoroquinolone antibiotic, ciprofloxacin, strongly stimulates biofilm formation in methicillin-resistant S. aureus, methicillin-sensitive S. aureus, and clinical isolates with diverse genetic backgrounds. Crystal violet staining indicated that ciprofloxacin induced a remarkable 12.46- to 15.19-fold increase in biofilm biomass. Confocal laser scanning microscopy revealed that ciprofloxacin induced denser biofilms. Phenotypic assays suggest that ciprofloxacin may enhance polysaccharide intercellular adhesin production, inhibit autolysis, and reduce proteolysis during the biofilm development, thus promoting initial adhesion and enhancing biofilm stability. Mechanistically, ciprofloxacin significantly alters the expression of various biofilm-related genes (icaA, icaD, fnbA, fnbB, eap, emp) and regulators (agrA, saeR). Gene knockout experiments revealed that deletion of agrC, rather than saeRS, abolishes the ciprofloxacin-induced enhancement of biofilm formation, underscoring the key role of agrC. Thermal shift assays showed ciprofloxacin binds purified AgrC protein, thereby inhibiting the Agr system. Molecular docking results further support the potential interaction between ciprofloxacin and AgrC. In summary, subinhibitory concentrations of ciprofloxacin stimulate S. aureus biofilm formation via an agrC-dependent pathway. This inductive effect may facilitate local infection establishment and bacterial persistence, ultimately leading to therapeutic failure.